Development of rubberised cementitious material incorporating graphene nanoplatelets and silica fume - Algaifi H.A.; Syamsir A.; Baharom S.; Alyami M.; Al-Fakih A.M.; Anggraini V. (Elsevier Ltd, 2024)
Rubberised cementitious material has gained significant attention within the civil engineering community. However, the gap and voids between rubber particles and cement gel remain challenge. To tackle these issues, silica fume (SF) and graphene nanoplatelets (GnPs) were used to enhance the microstructure of rubberised mortar at micro and nano scale levels. Silica fume was added at 20% of the cement weight, while, the inoculation of GnPs varied from 0.02% to 0.6% as cement replacement and the rubber powder ranged between 2% and 8% as sand replacement (by volume). The compressive (CS), flexural (FS), tensile (TS), ultrasonic pulse velocity (UPV), water absorption (WA) and porosity (P) of the proposed mortar were evaluated at the age of 28 days. The experimental and predicted outcome showed that the rubberised mortar incorporating SF and GnPs imparted superior properties compared to that of the control mixture for all rubber replacement percentage. For instance, when the rubber content was 5% and GnPs was 0.03%, the CS, FS, TS, UPV, WA and P were 45.51 MPA, 5.41 MPa, 3.13 MPa, 3.89 km/s, 5.23% and 7.22% compared to that of the control mortar without rubber (38.3 MPa, 4.1 MPa, 2.31 MPa, 3.65 km/s, 6.51% and 7.28%), respectively. FESEM also confirmed that the GnPs did not only acted as a filler material but also served as an impermeable barrier for continued crack propagation. It can be concluded that the inclusion of GnPs in rubberised cement-based material is considered as a sustainable choice in which it enhances its microstructure, specifically the interfacial transition zone (ITZ). 2023 The Authors